THE ROLE OF LAND DEED OFFICIALS IN THE DIGITAL TRANSFORMATION OF CERTIFICATE SERVICES: A REVIEW OF THE PERSPECTIVE OF LEGAL PROTECTION AND CERTAINTY - Noor, Aslan; Riansyah, Muhamad Rizki; Pratama, Yusril Hardiansyah; Pamungkas, Dwiky Hardika; Firdawuru, Seno Agung (Universitas Labuhanbatu, 2025)
Land Deed Making Officers are government partners in exercising authority in terms of making Land Transfer Deeds. This study aims to analyze the role and function of Land Deed Making Officers in the digital transformation of certificate services. In the perspective of protection and legal certainty. This study uses a normative legal research approach or also called library legal research. The results of the study show that the government in making policies needs to be balanced with efforts to strengthen human resources and technology. These efforts can be made by building an internet access network that reaches all regions of Indonesia and providing training to Civil Service employees at the Ministry of ATR/BPN and other supporting parties such as Land Deed Making Officers and notaries. This will provide protection and legal certainty for certificate holders.Keywords: Land Deed Making Officer; Digital; Certificate; Protection; Legal Certainty